DIDACTIZATION OF EPONYMOUS PROVERBS IN BINJA-SOUTH: THE CASE OF WASIMBA WA MARINGA SECTOR - Kalume Bushiri Valentin,; Et Kasongo Mwanga Lucien2, (IJRDO - Journal of Social Science and Humanities Research, 2025)
This study focuses on the didactic use of eponymous proverbs from the Binja-Sud region, specifically within the Wazimba wa Maringa sector. Proverbs, as cultural and linguistic expressions, play a key role in transmitting knowledge, values, and communal identity. However, their inclusion in educational curricula remains limited. The main aim of this research is to demonstrate how these proverbs, rich in moral and social teachings, can be pedagogically used in the classroom, particularly in language (French and local languages), literature, and civic education instruction. The methodology combines an ethnolinguistic and didactic approach, based on data collected from elders, teachers, and learners in the Wazimba wa Maringa area. The analysis reveals that eponymous proverbs can serve as tools for contextualization, motivation, and awareness of local cultural wealth. In short, the didactic integration of Binja-Sud's eponymous proverbs offers an opportunity to promote indigenous knowledge and strengthen education rooted in local culture, while developing learners’ language and critical thinking skills.